Spontaneous Hemopericardium Leading to Cardiac Tamponade in a Patient with Essential Thrombocythemia - Anand Deshmukh; Shanmuga P. Subbiah; Sakshi Malhotra; Pooja Deshmukh; Suman Pasupuleti; Syed Mohiuddin (Cardiology Research and Practice)
Acute cardiac tamponade requires urgent diagnosis and treatment. Spontaneous hemopericardium leading to cardiac tamponade as an initial manifestation of essential thrombocythemia (ET) has never been reported in the literature. We report a case of a 72-year-old Caucasian female who presented with spontaneous hemopericardium and tamponade requiring emergent pericardiocentesis. The patient was subsequently diagnosed to have ET. ET is characterized by elevated platelet counts that can lead to thrombosis but paradoxically it can also lead to a bleeding diathesis. Physicians should be aware of this complication so that timely life-saving measures can be taken if this complication arises.